Strategic plan for Davao Laundry Plus - Estrellado,Maria Lourdes L.; Gomez, Aurelia Luzviminda V.; Soledad, Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2005)
This paper aimed to formulate a strategic plan for Davao Laundry Plus (DLP) using the strategic management framework outlined by Pearce and Robinson (2000) with slight modifications to accommodate the thoughts of other authorities in strategic management such as Cole (1997), Mintzberg et. Al (1995) and David (2001). In formulating the strategic options for DLP, a thorough analysis of the environmental factors affecting and influencing the company was made. Its internal environment was examined by first, dividing it into four areas: Organization, Human Resource, Marketing and Finance and, then, analyzing each area to identify the strengths and weaknesses of the organization. Similarly, the external environment was first, subdivided into three: the remote, industry and operating environments, after which each environmental sector was analyzed to identify the opportunities and threats that DLP will most likely face in its external environment from 2005 to 2009. The researcher noted the following as DLP?s strengths: capable management, high liquidity, profitable operation, a loyal customer base, and high quality service. Moreover, the following opportunities open to the company were identified: a favorable change in Davao City's business environment, favorable change in people's psychographic factors and the affordability of higher capacity laundry machines. Davao Laundry Plus, on the hand, is impaired by three weaknesses. These are high personnel turnover, fluctuating net income growth rate and its reactive form of marketing. Also, most likely, it will face the threats of having a low entry barrier in the industry, increasing number of laundry businesses and the predatory pricing of current and potential competitors. The results of the environmental analyses indicated a need to modify the corporate objectives of the company. Hence, this researcher now proposes the following as corporate objectives: Vision: Davao Laundry Plus aims to capture business and market leadership in providing laundry services that is centered on a culture of excellence consciously steered by its values system of teamwork, accountability, sense of ownership, diligence and courtesy. Mission: Davao Laundry Plus guarantees a higher degree of customer satisfaction through the delivery of the highest quality of service performed by highly skilled and amply compensated happy staff using state-of-the-art laundry equipment as an auxiliary to increasing Company wealth while returning a portion of its gains to the Community it operates. Goals for the next 5 years, 1. To increase market share and profitability, DLP will set-up at least 10 additional branches within Davao City and nearby areas. 2. To have a net income growth rate of 20% per annum. Strategic options were identified using the SWOT matrix analysis. These options were then ranked according to their compatibility with the firm's resources and the major issues enveloping it through the aid of the Quantitative Strategic Planning Matrix (QSPM). Six strategic options were considered: Business and Market Expansion, Horizontal Integration, Product Development, Intensify Marketing Efforts, Concentric Diversification and the Retention of Skilled Personnel. Of these, the Business and Market Expansion option, which garnered a Total Attractiveness Score of 7.09 in the QSPM, was chosen as the best strategic choice for DLP and the option most consistent with DLP?s corporate objectives. An implementation program incorporating both schedule and needed resources for each activity is presented. This was drawn with the end in view being the alignment of the implementing program with the chosen strategy. This paper ends with a discussion of the strategic control systems that this researcher feels need to be put in place to monitor Davao Laundry Plus? execution of the proposed implementation program. The company's movement and pace towards its goals are monitored using key result areas (KRAs) and performance indicators (PIs). This control system was put together with these fundamental perspectives in mind: strategic and operational control and continuous improvement through Total Quality Management (TQM).
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, April 2005
Keywords: Strategic plan